2012
DOI: 10.1121/1.3701984
|View full text |Cite
|
Sign up to set email alerts
|

Binaural loudness summation for speech presented via earphones and loudspeaker with and without visual cues

Abstract: Preliminary data [M. Epstein and M. Florentine, Ear. Hear. 30, 234-237 (2009)] obtained using speech stimuli from a visually present talker heard via loudspeakers in a sound-attenuating chamber indicate little difference in loudness when listening with one or two ears (i.e., significantly reduced binaural loudness summation, BLS), which is known as "binaural loudness constancy." These data challenge current understanding drawn from laboratory measurements that indicate a tone presented binaurally is louder tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
(62 reference statements)
1
21
0
Order By: Relevance
“…They hypothesized that the brain is able to take source position into account to achieve loudness constancy when distance is varied. Loudness constancy was also observed by Epstein and Florentine (2012) for monaural to binaural listening situations, but could only be achieved when increasing the ecological validity of the monaural listening by providing visual cues. The possible effect of lateralization on loudness might be largely dependent on the experimental conditions, if caused by similar high-level processes, which might explain the discrepancies between studies conducted using loudspeakers and headphones.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…They hypothesized that the brain is able to take source position into account to achieve loudness constancy when distance is varied. Loudness constancy was also observed by Epstein and Florentine (2012) for monaural to binaural listening situations, but could only be achieved when increasing the ecological validity of the monaural listening by providing visual cues. The possible effect of lateralization on loudness might be largely dependent on the experimental conditions, if caused by similar high-level processes, which might explain the discrepancies between studies conducted using loudspeakers and headphones.…”
Section: Discussionmentioning
confidence: 74%
“…The level of a monaural stimulus needs to be increased by 3 dB near threshold but by 6-10 dB at high levels to be matched in loudness with its binaural equivalent. However, Epstein and Florentine (2012) argue that such differences are only due to the fact that monaural stimuli are not ecologically valid. They showed that increasing the ecological validity of monaural listening by providing visual cues significantly reduced these differences.…”
Section: Introductionmentioning
confidence: 94%
“…probably be even smaller for everyday sounds like speech (Epstein and Florentine, 2012). It can be concluded that only minor gain adjustments would be required to equate loudness for unilateral and bilateral hearing-aid fittings.…”
Section: Discussionmentioning
confidence: 98%
“…There is some evidence that binaural summation of loudness is influenced by the specific listening conditions, perhaps depending on relatively high-level cognitive factors. Epstein and Florentine (2012) showed that binaural loudness summation was significantly less for speech presented via a loudspeaker with visual cues than for speech presented via earphones with visual cues, and for speech presented via a loudspeaker or earphones without visual cues. Binaural loudness summation is also smaller for speech than for artificial stimuli like tones (Epstein and Florentine, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…This prediction is supported by electrophysiological experiments where the response evoked binaurally is in fact equal to larger of two responses evoked monaurally [34] (see figure in appendix). Similarly, assuming that loudness perception is linked to the length of the interval, a possible psychophysical analog is that a tone presented binaurally is perceived to be less than twice as loud as monaural stimulation [35]. In both examples, the apparent sublinear effects arises from the properties of addition operation, and may not necessarily be due to inhibitory processes.…”
Section: Implications For Experimental Data and Computational Modelsmentioning
confidence: 99%